To Study the Effects of the PNF Stretching and Stabilization Exercises on the Improvement of Pain and Spastic Shoulder in Hemiplegic Patients: A Comparative Study: Life Sciences-Physiotherapy - Larissa Dhar; S.Anita Devi; Trishna Saikia Baruah; Abhijit Dutta (International Journal of Life Science and Pharma Research, 2022)
Stroke is the leading cause of adult disability and inpatient rehabilitation admissions. The WHO definition of stroke is rapidly developing clinical signs of focal (global) disturbance of cerebral function, with symptoms lasting 24hours or longer or leading to death, with no apparent cause other than of vascular origin: it includes patients presenting clinical signs and symptoms suggestive of subarachnoid haemorrhage, intracerebral haemorrhage or cerebral ischemic necrosis. An estimated 70% of the patients who survive a stroke are unable to use their limbs (Upper Limb/Lower Limb) independently during the first three to four weeks post stroke. Patients who have suffered a stroke experience loss, uncertainty, and social isolation, as stroke represents a sudden, overwhelming, and fundamental change for the survivor. Personal control over progressoptimism, and fears of dependency, as well as markers of independence and interaction with therapists, were identified as important factors influencing recovery. Effective rehabilitation strategies are of utmost concern to different parts of the health care system. Their value resides both in giving people affected by stroke the best possible opportunity for their recovery as individuals and in offering health organizations the best use of limited finances and resources. The objective of the study was to compare the effectiveness of PNF(Proprioceptive Neuromuscular Fascilitation) stretching and stabilizations exercises techniques in the improvement of pain and spastic shoulder.30 post stroke patients (affected for a period of more than 6months), 40-60 years of age were randomly assigned to PNF stretching and stabilization exercises were collected on Day 0, DAY 90. Paired t-test were used for statistical interventions. Assessment of Visual Analogue Scale (VAS) and Modified Ashworth Scale were performed. Analysis of scores showed significant improvement (p<0.02) overtime within the groups and inter group analysis showed statistical significance. The study concluded that PNF Stretching technique is better than Stabilization techniques in improving pain and spastic shoulder in chronic stroke patients.